2023
DOI: 10.3390/nano13091491
|View full text |Cite
|
Sign up to set email alerts
|

Fast-Response Micro-Phototransistor Based on MoS2/Organic Molecule Heterojunction

Abstract: Over the past years, molybdenum disulfide (MoS2) has been the most extensively studied two-dimensional (2D) semiconductormaterial. With unique electrical and optical properties, 2DMoS2 is considered to be a promising candidate for future nanoscale electronic and optoelectronic devices. However, charge trapping leads to a persistent photoconductance (PPC), hindering its use for optoelectronic applications. To overcome these drawbacks and improve the optoelectronic performance, organic semiconductors (OSCs) are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…By constructing such weakly interacting TMDC/TPc heterostructures, the photoresponsivity and response time in phototransistors were improved compared to the pure TMDC components. Furthermore, TPcs could be used for defect engineering and the resulting enhancement of photoluminescence quantum yields. In this work, we seek to modify the type and concentration of charge carriers in n-type MoS 2 by the adsorption of cobalt phthalocyanine (CoPc) and its perfluorinated derivative (CoPcF 16 ). While the interface between TMDCs and other TPcs has been explored previously, the detailed electronic structure in interfaces between cobalt phthalocyanine derivatives and MoS 2 has not been studied so far .…”
Section: Introductionmentioning
confidence: 99%
“…By constructing such weakly interacting TMDC/TPc heterostructures, the photoresponsivity and response time in phototransistors were improved compared to the pure TMDC components. Furthermore, TPcs could be used for defect engineering and the resulting enhancement of photoluminescence quantum yields. In this work, we seek to modify the type and concentration of charge carriers in n-type MoS 2 by the adsorption of cobalt phthalocyanine (CoPc) and its perfluorinated derivative (CoPcF 16 ). While the interface between TMDCs and other TPcs has been explored previously, the detailed electronic structure in interfaces between cobalt phthalocyanine derivatives and MoS 2 has not been studied so far .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the requirement of more complex layered structures and high cost, there has been a few researches in recent years to explore developments in the field of photodetectors based on phototransistor structures (the mainstream structure of a photodetector is the PN or PIN structure). 16 It should be noted that with a gate, the gate oxide can be classified as a phototransistor. Because at thermal equilibrium, the Fermi levels of the two different materials should be equal and the vacuum level must also be continuous, the junction of the metal−semiconductor forms a Schottky barrier with a rectifying effect.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the requirement of more complex layered structures and high cost, there has been a few researches in recent years to explore developments in the field of photodetectors based on phototransistor structures (the mainstream structure of a photodetector is the PN or PIN structure) . It should be noted that with a gate, the gate oxide can be classified as a phototransistor.…”
Section: Introductionmentioning
confidence: 99%
“…One economical and efficient approach is to create heterojunctions, including TMD-TMD [10][11][12] and molecule-TMD heterojunctions. [10][11][12][13][14] For example, it was recently shown that many-body control of electron localization in moiré heterostructures can greatly improve catalytical performance 15 . Similarly, doping monolayer TMD with molecules could control interfacial band alignment and its chemical and electrostatic environments 16 .…”
Section: Introductionmentioning
confidence: 99%